2016
DOI: 10.1089/ham.2015.0120
|View full text |Cite
|
Sign up to set email alerts
|

Managing High-Altitude Pulmonary Edema with Oxygen Alone: Results of a Randomized Controlled Trial

Abstract: Yanamandra, Uday, Velu Nair, Surinderpal Singh, Amul Gupta, Deepak Mulajkar, Sushma Yanamandra, Konchok Norgais, Ruchira Mukherjee, Vikrant Singh, Srinivasa A. Bhattachar, Sagarika Patyal, and Rajan Grewal. High-altitude pulmonary edema management: Is anything other than oxygen required? Results of a randomized controlled trial. High Alt Med Biol. 17:294-299, 2016.-Treatment strategies for management of high-altitude pulmonary edema (HAPE) are mainly based on the observational studies with only two randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…7,8 If they were not treated in time, a systemic alveolar edema will develop, when the effectiveness of high-flow oxygen therapy will be greatly compromised. On the contrary, an early low-flow oxygen inhalation shows a good therapeutic effect, 12 no matter whether the general pulmonary vasoconstriction occurs or not (figure).…”
Section: Oxygen Maintains Hypoxic Pulmonary Vasoconstrictionmentioning
confidence: 99%
“…7,8 If they were not treated in time, a systemic alveolar edema will develop, when the effectiveness of high-flow oxygen therapy will be greatly compromised. On the contrary, an early low-flow oxygen inhalation shows a good therapeutic effect, 12 no matter whether the general pulmonary vasoconstriction occurs or not (figure).…”
Section: Oxygen Maintains Hypoxic Pulmonary Vasoconstrictionmentioning
confidence: 99%
“…One randomized clinical trial and one case-control study showed that supplemental oxygen treatment at low flow rates with bed rest is an effective alternative of descent 51 , 52 . Therefore, along with bed rest, use of supplemental oxygen to maintain an oxygen saturation level above 90% is recommended to resolve the symptoms 1 , 10 …”
Section: Treatmentmentioning
confidence: 99%
“…Although one non-randomized, experimental study showed that nifedipine may be helpful for treatment of HAPE, 56 a case-control study and another randomized controlled study in more recent years, showed that nifedipine with supplemental oxygen was not superior to treatment with supplemental oxygen only 52 , 57 . However, based on clinical experience, 30 mg nifedipine twice daily is suggested when oxygen is not available and descent is not possible 10 …”
Section: Treatmentmentioning
confidence: 99%
“…HAPE is initially treated with supplemental oxygen, if available, and rest followed by expeditious descent. Recent evidence showed a 95% success rate in treatment of HAPE at moderate altitude with oxygen and rest alone (Yanamandra et al, 2016). In cases when pulmonary edema does not respond to classic intervention, other etiologies must be considered.…”
Section: Introductionmentioning
confidence: 99%